Sacrament and Model: Christology, Soteriology, and the Eucharist in Augustine’s De Trinitate 4 and Expositions of Psalm 22 - Zerra, Luke (Anglican theological review, 2025)
This article reads book 4 of the De trinitate alongside Augustine?s commentaries on Psalm 22?Psalm 21 in the translations used by Augustine?to shed light on the Christology he develops in book 4 of De trinitate. By reading these texts alongside each other, I offer the interpretative claim that Augustine develops a Christology and soteriology centered on participation in the divine life, and that the Eucharist is a key sign of this participation. Augustine?s expositions of Psalm 21(22) clarify Augustine?s view of Christ?s mediating role, showing that salvation is found in the Church?s participation in Christ, a point that is visibly revealed in the Eucharist. Augustine?s commentaries on Psalm 21(22) thus shed light on the Christology and soteriology developed in De Trinitate. Book 4, drawing several elements together under the central category of the Eucharist.